Comparison of an HPLC-MS/MS Method with Multiple Commercial ELISA Kits on the Determination of Levels of 8-oxo-7,8-Dihydro-2'-Deoxyguanosine in Human Urine - Kun-Ming Chen; Ana Calcagnotto; Junjia Zhu; Yuan-Wan Sun; Karam El-Bayoumy; John P. Richie Jr (Journal of New Developments in Chemistry, 2018)
Introduction: Analysis of 8-oxodG is usually conducted by either chromatography-based methods or by immunochemical methods commonly used based upon their low cost and high-throughput. However, concern regarding the accuracy of ELISA methods has complicated their use. We directly compare the levels of urinary 8-oxodG obtained by HPLC-MS/MS with three commercially available ELISA kits in this report. Methods: In the current study, a total of 9 human urine samples were analyzed by LC-MS/MS and three commonly used commercial available ELISA kits. Results: We found that urinary 8-oxodG levels analyzed by HPLC-MS/MS [1.4 ± 0.3 nmol/mmol creatinine) were 7.6- to 23.5-fold lower than those detected by ELISA. Overall, the correlations between ELISA and HPLC-MS/MS were poor but were improved after SPE purification for kits from ENZO (P = 0.2817 without SPE; P = 0.0086 with SPE) and Abcam (P = 0.0596 without SPE; P = 0.0473 with SPE). Discussion and Conclusion: While we confirmed that SPE purification can improve the correlation between the selected ELISA kits and HPLC-MS/MS, HPLC-MS/MS is still the method of choice to accurately assess the levels of 8-oxodG in human urine.
Keywords: 8-oxo-7